2021
DOI: 10.1109/tmech.2020.3009384
|View full text |Cite
|
Sign up to set email alerts
|

Pulling Illusion Based on the Phase Difference of the Frequency Components of Asymmetric Vibrations

Abstract: When presented with asymmetric vibrations, humans experience an illusory force, similar to the sensation of being pulled in a particular direction. A pulling illusion has also been used in new display elements for a virtual reality content and a pedestrian navigation system. However, the basic design of asymmetric vibration stimuli that can induce this illusion has not yet been determined. In particular, it is unclear as to which part of the vibration waveform should be asymmetric to induce an illusion. To bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 19 publications
(38 reference statements)
6
21
0
Order By: Relevance
“…We confirmed that the illusion can be induced by presenting the asymmetric vibrations that consists of two frequency components [18]. The basic model of the asymmetric vibration based on this finding is as follows:ẍ…”
Section: Stimulisupporting
confidence: 75%
See 4 more Smart Citations
“…We confirmed that the illusion can be induced by presenting the asymmetric vibrations that consists of two frequency components [18]. The basic model of the asymmetric vibration based on this finding is as follows:ẍ…”
Section: Stimulisupporting
confidence: 75%
“…In addition, in the basic model of the asymmetric vibration (Equation 1), we confirmed the effects of the phase difference at 75 Hz [18]. Thus, the main frequencies at which the illusion occurred were 40 Hz [6,8] and 75 Hz [9,18]. In this experiment, the fundamental frequency f was 40 Hz and 75 Hz (2 levels) because the illusion occurred at these frequencies.…”
Section: Stimulisupporting
confidence: 70%
See 3 more Smart Citations